2021
DOI: 10.1016/j.jped.2020.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The value of oxygen index and base excess in predicting the outcome of neonatal acute respiratory distress syndrome

Abstract: Objective This study aimed to identify the predictors and threshold of failure in neonatal acute respiratory distress syndrome. Methods Newborns with severe acute respiratory distress syndrome aged 0–28 days and gestational age ≥36 weeks were included in the study if their cases were managed with non-extra corporal membrane oxygenation treatments. Patients were divided into two groups according to whether they died before discharge. Predictors of non-extra corporal memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…6 Moreover, OI was investigated as a prognostic tool for acute HRF in neonates. 7,8 However, the OI can be calculated in an intubated infant, needs mechanical ventilation, and requires an indwelling arterial catheter or arterial puncture. The severity of hypoxemia from OI is intermittently determined when arterial blood gas (ABG) samplings are obtained.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…6 Moreover, OI was investigated as a prognostic tool for acute HRF in neonates. 7,8 However, the OI can be calculated in an intubated infant, needs mechanical ventilation, and requires an indwelling arterial catheter or arterial puncture. The severity of hypoxemia from OI is intermittently determined when arterial blood gas (ABG) samplings are obtained.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“… 2 A multicentre study in China reported that the mortality rate of severe neonatal ARDS with a gestational age (GA) ≥36 weeks was 25·2%. 3 Compared with neonatal respiratory distress syndrome (RDS) incurred by primary pulmonary surfactant deficiency, neonatal ARDS may be more likely to affect late-preterm and full-term infants. 3 , 4 However, the aetiology and pathogenesis of neonatal ARDS remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 3 Compared with neonatal respiratory distress syndrome (RDS) incurred by primary pulmonary surfactant deficiency, neonatal ARDS may be more likely to affect late-preterm and full-term infants. 3 , 4 However, the aetiology and pathogenesis of neonatal ARDS remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Base excess (BE) is defined as the amount of acid or alkali needed to adjust the value to the normal range ( 3 ), which is considered a pure indicator of metabolic acid–based balance ( 4 ). Base excess has been widely used as a predictor for the diagnosis of neonatal sepsis in pre-term newborns ( 5 ), complications in cytoreductive surgery ( 6 ), or the prognosis of neonatal acute respiratory distress syndrome ( 7 ). The indicator also shows significant representativeness in heart failure ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%